Development of Math Modules Based on Active Learning Type the Power of Two using Ms. Word in the Junior High School Curriculum - Zattira Nadira Rahma; Moh. Mahfud Effendi; Alfiani Athma Putri Rosyadi (STAI Hubbulwathan Duri, 2023)
Modules in learning emphasize more on the activeness and activity of students. This study aims to develop a mathematics module based on an Active Learning (AL) strategy with the Active Learning (AL) type, namely The Power of Two (PT). This study uses an RD research design with the ADDIE model, which consists of 5 stages: analysis, design, development, implementation, and evaluation. This study involved three validators in assessing the validity of the module and 12 small group students to test student responses to the module, which was used to determine the practicality of the module. Based on the research results, it is known that the module developed has very valid criteria, with a percentage of 91.48% by two expert lecturers and a mathematics teacher. The results of student response tests used to assess the practicality of the developed module have very practical criteria, with a percentage of 90.22% by students. This shows that the mathematics module developed based on an Active Learning (AL) strategy with The Power of Two (PT) type is very valid and very practical.